2009
DOI: 10.1007/s11434-008-0566-0
|View full text |Cite
|
Sign up to set email alerts
|

Determination of optimum operating conditions for production of polyhydroxybutyrate by activated sludge submitted to dynamic feeding regime

Abstract: Polyhydroxybutyrate (PHB) was produced by activated sludge in a two-stage process. In the first stage, the sludge with high storage potential was enriched in a sequencing batch reactor (SBR) operated by a dynamic feeding regime. The biosynthesis of PHB was sequentially accomplished in a batch reactor in the second stage. This article focused on the optimization of PHB content by evaluating the effects of three critical factors: Dissolved oxygen, pH and food-to-microorganism (F/M) ratio in the batch reactor. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…(Fig. 2) The increase of reaction pH during the PHA accumulation stage has been reported by several researchers (Chua et al, 2003;Serafim et al, 2004;Qu et al 2009;Albuquerque et al, 2011). Dias et al (2006) has concluded that three processes affect the reaction pH: uptake of the substrate (decrease the concentration of H + in the solution), NH 3 assimilation and CO 2 production and transfer (both increase the concentration of H + in the solution).…”
Section: Do and Reaction Ph Variation In Accumulation Assaysmentioning
confidence: 59%
“…(Fig. 2) The increase of reaction pH during the PHA accumulation stage has been reported by several researchers (Chua et al, 2003;Serafim et al, 2004;Qu et al 2009;Albuquerque et al, 2011). Dias et al (2006) has concluded that three processes affect the reaction pH: uptake of the substrate (decrease the concentration of H + in the solution), NH 3 assimilation and CO 2 production and transfer (both increase the concentration of H + in the solution).…”
Section: Do and Reaction Ph Variation In Accumulation Assaysmentioning
confidence: 59%
“…By contrast, another previous study focussing on PHB production by activated sludge in a two-stage 169 process revealed that the rate of substrate uptake, as well as the yield and content of PHB increased 170 with an increase in DO concentration. [12] The studies reported by Qu and Liu [12] also showed that an 171 enhanced F/M ratio favored PHB accumulation. 172 173…”
Section: Walls 158mentioning
confidence: 95%
“…[11] 71 4 Many studies have been carried out on activated sludge to produce PHA, most of them using feast-72 famine regimes or nutrient pulses. [12] It has been observed that its production depends on operational 73 parameters such as the type of carbon source, C/N ratio, organic load, dissolved oxygen (DO) 74 concentration, pH, sludge retention time (SRT), temperature, magnetic field intensity, and nutrient 75 deficiencies such as nitrogen and phosphorus. [13][14][15] 76 There is currently great interest worldwide to produce various commercially usable macromolecules 77 from the WAS from sewage treatment plants.…”
Section: Introduction 41 42mentioning
confidence: 99%
“…Activated sludge can be an alternative to pure cultures for PHA production due to many PHA-producing bacteria present in activated sludge (Yang et al, 2013 ). In the wastewater treatment process, the microorganisms from activated sludge display the ability to transform a biodegradable carbon source into PHA before using them for growth (Qu and Liu, 2009 ). Industrial-scale PHA production is based mainly on pure-culture systems with refined feedstock and sterile cultivation conditions.…”
Section: Trends Unveiledmentioning
confidence: 99%
“…Later studies (after 2000) focus on parameters such as carbon and nitrogen sources, their mutual quantitative relations in the fermentation reaction, and the impact of these parameters on process efficiency (Khardenavis et al, 2005 ). Further analysis on the example of PHB production describes the impact of critical factors such as dissolved oxygen, pH, and food to microorganism (F/M) ratio in the batch reactor on the reaction efficiency (Qu and Liu, 2009 ). Researchers also carried out physiochemical properties analysis of the polymers PHB and P(HB-co-HV) to identify production conditions that directly affect final product mechanical properties (Wallen and Rohwedder, 1974 ; Patel et al, 2009 ).…”
Section: Trends Unveiledmentioning
confidence: 99%